G W ORIONIS A 20 000 YEARS OLD T TAURI STAR? - POVEDA, ARCADIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1969)
GW Ori is a T Tauri type star whose magnitude and spectral type have been determined by Joy and Wilson. From their data we obtain the luminosity, radius and effective temperature which allows to locate it in the H-R diagram and compare its position with H
BOL OBS TONAN TACUB
Keywords: ORIONIS, TAURI STAR; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS